Проблеми вітчизняного машинобудування та можливі шляхи виходу з кризи - Гармаш, Сергій Володимирович (Henan Science and Technology Press, 2016)
У статті аналізуються показники розвитку машинобудівної галузі України у динаміці за певний період часу, які стали наслідком змін, притаманних соціально-економічному розвитку країни за роки незалежності. Проводиться порівняльний аналіз зі станом машинобудівної галузі у інших країнах, зокрема у Китаї, пропонуються можливі шляхи виходу із кризи, що склалася.

Activities of machine building industry development in Ukraine during the certain period of time which became the consequences under the changes attached to the socioeconomic development of the country during the years of independence are analyzed in this paper. Comparative analysis with the state of machine building industry in other countries, in particular in China, is drawn. Possible ways for overcoming the crisis are proposed.
Problems of domestic machine building industry and possible ways of overcoming the crisis
Keywords: problems of domestic machine building industry; socioeconomic formation; crisis; direct foreign investment; проблеми вітчизняного машинобудування; оціально-економічна формація; криза; прямі іноземні інвестиції; інвестиції; машинобудування